К вопросу о проблеме диагностики и развития одаренных детей в условиях взаимодействия «Школа-Вуз» - Гребенникова, Вероника Михайловна; Щербина, Анна Ивановна (International Dialogues on Education Journal, 2016)
The article deals with the problem of diagnosing gifted children and creating psychological and pedagogical conditions for the intellectual and personal growth of gifted children in secondary schools and higher-education institutions. The overriding goal of training and education is to provide conditions for recognizing and developing all children` s abilities and talents, and their subsequent implementation in professional activities. To become a condition for individual personal development any creative activity of a child in different types of leisure activities should be properly organized. Conditions for the optimal development of gifted younger students were created in a framework of “school-university” interactive summer activities Working in such a creative socio-cultural space, through direct interaction with exceptional children in students` practica, will contribute to a mature, professionally oriented personality of future teachers.